2013
DOI: 10.1097/pdm.0b013e31827630b8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diagnosis in Recently Transfused Patients

Abstract: Analysis of recently transfused patients is usually postponed to avoid spurious results because of contamination with donor's cells. However, little is known about the extent of this influence in routine molecular diagnostic tests. To elucidate this question, we tested a mix of blood samples from 2 α-1-antitrypsin-deficient patients diagnosed as Pi*Z homozygous with 1 normal donor at 1:1, 1:10, 1:20, and 1:30 proportions. Human identification panel and Pi*Z allele detection were used to establish the detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Lymphocytes are typically utilized to perform molecular analyses from peripheral blood, but some patients with sAA may not have an adequate absolute lymphocyte count to permit these analyses. Additionally, if a patient receives blood transfusions, analysis could be confounded by donor DNA in the peripheral blood or saliva (which can have hematopoietic contamination) and lead to erroneous results, even though this is infrequent (Mardini et al, 2013) and was not observed in our cohort. While germline genetic testing on skin fibroblasts is a standard recommendation for pediatric MDS (DiNardo et al, 2016), it is not for sAA or BMF likely due to less acquired clonal changes in the marrow and peripheral blood.…”
Section: Future Considerationsmentioning
confidence: 93%
“…Lymphocytes are typically utilized to perform molecular analyses from peripheral blood, but some patients with sAA may not have an adequate absolute lymphocyte count to permit these analyses. Additionally, if a patient receives blood transfusions, analysis could be confounded by donor DNA in the peripheral blood or saliva (which can have hematopoietic contamination) and lead to erroneous results, even though this is infrequent (Mardini et al, 2013) and was not observed in our cohort. While germline genetic testing on skin fibroblasts is a standard recommendation for pediatric MDS (DiNardo et al, 2016), it is not for sAA or BMF likely due to less acquired clonal changes in the marrow and peripheral blood.…”
Section: Future Considerationsmentioning
confidence: 93%